Assessing environmental education through KBSM social sciences subjects: Three case studies - Chong S.T.; Ng Y.J.; Loh K.S.; Rahman A.Z.A. (Science and Engineering Research Support Society, 2023)
The issue of flood disaster is becoming more prevalent in the present days of Malaysia. Flood is an annual recurring problem and it causes issues of discomfort, economic loss, health and the social well-being of Malaysians. To cope with this hydrometeorological disaster, the authoritative Sendai Framework for Disaster Risk Reduction 2015-2030 (2015) (Hereafter Sendai Framework) identified education as one of the best avenues to cope with flood disaster. This paper focuses on the 4th priority area in the Sendai Framework which aims is enhancing disaster preparedness for effective response and to Build Back Better in recovery, rehabilitation and reconstruction. Hence, this paper examines flood education through KBSM social sciences subjects with the idea that the Malaysian secondary school curriculum can help to enhance the preparedness among the students. The social sciences subjects chosen are Geography, English and Moral studies in Malaysian school system. The aim of this paper is to examine the coverage of flood related issues in the KBSM textbooks as well as the ways in which the issues are being discussed and manifested. The methodology used is qualitative content analysis. The findings indicate that in the Malaysian secondary school curriculum, English textbooks have more flood related topics than Moral studies and Geography. The issues discussed in the English textbooks are very current, varied and able to elucidate the synergy of knowledge. 2019 SERSC.